Oropouche virus cases identified in Ecuador using an optimised qRT-PCR informed by metagenomic sequencing. - Emma L Wise; Sully Márquez; Jack Mellors; Verónica Paz; Barry Atkinson; Bernardo Gutierrez; Sonia Zapata; Josefina Coloma; Oliver G Pybus; Simon K Jackson; Gabriel Trueba; Gyorgy Fejer; et al. (Public Library of Science (PLoS), 2020)
Oropouche virus (OROV) is responsible for outbreaks of Oropouche fever in parts of South America. We recently identified and isolated OROV from a febrile Ecuadorian patient, however, a previously published qRT-PCR assay did not detect OROV in the patient sample. A primer mismatch to the Ecuadorian OROV lineage was identified from metagenomic sequencing data. We report the optimisation of an qRT-PCR assay for the Ecuadorian OROV lineage, which subsequently identified a further five cases in a cohort of 196 febrile patients. We isolated OROV via cell culture and developed an algorithmically-designed primer set for whole-genome amplification of the virus. Metagenomic sequencing of the patient samples provided OROV genome coverage ranging from 68-99%. The additional cases formed a single phylogenetic cluster together with the initial case. OROV should be considered as a differential diagnosis for Ecuadorian patients with febrile illness to avoid mis-diagnosis with other circulating pathogens.